A Rare Complication following Thyroid Percutaneous Ethanol Injection: Plummer Adenoma - Roberto Cesareo; Anda Mihaela Naciu; Valerio Pasqualini; Giuseppe Pelle; Silvia Manfrini; Gaia Tabacco; Angelo Lauria Pantano; Alessandro Casini; Roberto Cianni; Andrea Palermo (Case Reports in Endocrinology)
Percutaneous ethanol injection (PEI) is a technique used only for benign thyroid nodules, cystic or mixed cystic-solid with a large fluid component. It is a quite low-cost, safe, and outpatient method of treatment. Rare and severe complications have been described after PEI: jugular vein thrombosis and severe ethanol toxic necrosis of the larynx combined with necrotic dermatitis. Moreover, only four thyrotoxicosis cases due to Graves’ disease have been reported. We report a case of 58-year-old female with a voluminous thyroid cystic nodule, occupying almost the entire left thyroid lobe. Our patient had already performed surgical visit and intervention of thyroidectomy had been proposed to her, which she refused. At baseline, our patient has a normal thyroid function with negative autoantibodies. According to the nodular structure, intervention of PEI has been performed with a significant improvement of compressive symptoms and cosmetic disorders. About 30 days after treatment, there was a significant volume reduction, but patient developed an acclaimed symptomatic thyrotoxicosis. After ruling out several causes of hyperthyroidism and according to the thyroid scintigraphy findings, we made the diagnosis of Plummer adenoma. To our knowledge, our patient is the first case of Plummer adenoma following PEI treatment of nontoxic thyroid nodule.